2016
DOI: 10.1002/jsfa.8144
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and food pathogens: impact of biologically active aflatoxins and their control strategies

Abstract: Globally disease outbreaks as a result of the consumption of contaminated food and feedstuffs are a regular primary problem. The foremost elements contributing to contamination are microorganisms, particularly fungi, which produce low-molecular weight secondary metabolites, with demonstrated toxic properties that are referred to as mycotoxins. Aflatoxins contaminate agricultural commodities and may cause sickness or fatality in humans and animals. Moreover, poor conditions of storage and a deficiency in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…India, Iran, Brazil, Turkey, and Egypt) were developing countries as defined by the United Nations, which suggests that each perceive this issue as a serious problem. Among this grouping, there was international diversity not associated [58,59], Iran [60], India [61][62][63][64], Brazil [51,65], and Egypt [66]) caused exceptionally large morbidity and mortality connected with such outbreaks [1,[67][68][69], and this may explain why more research has emphasized on aflatoxin since that time [28]. Analysis of international collaborations (i.e., link strength) showed that the United States had the highest number of collaborators (n = 87) followed by the United Kingdom (n = 63), and Italy (n = 54) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…India, Iran, Brazil, Turkey, and Egypt) were developing countries as defined by the United Nations, which suggests that each perceive this issue as a serious problem. Among this grouping, there was international diversity not associated [58,59], Iran [60], India [61][62][63][64], Brazil [51,65], and Egypt [66]) caused exceptionally large morbidity and mortality connected with such outbreaks [1,[67][68][69], and this may explain why more research has emphasized on aflatoxin since that time [28]. Analysis of international collaborations (i.e., link strength) showed that the United States had the highest number of collaborators (n = 87) followed by the United Kingdom (n = 63), and Italy (n = 54) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxins are primarily produced by Aspergillus spp., including A. flavus, as polyketide secondary metabolites. These opportunistic fungi are commonly detected as contaminants in cereal crops at both the pre-and post-harvest stages (Umesha et al, 2017). Although aflatoxigenic fungi more commonly grow in tropical and sub-tropical climates, aflatoxin contamination has always been a global concern owing to globalized trade; moreover, zones with a perennial aflatoxin contamination risk have expanded owing to climate change (Marroquín-Cardona et al, 2014;Baranyi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are capable of producing compounds that could either repress pathogenesis by inhibiting filamentation or enhance fungal virulence determinants [5]. Co-existence of two major pathogens, such as Aspergillus flavus and Listeria monocytogenes, has been reported in food systems such as dairy products, eggs, meats, and brewer's grain [6][7][8][9][10]. The interactions between those two pathogens are critical in shaping the food microbial communities and exert a significant impact on the colonization, survival and even pathogenesis of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%